WOMEN’S EMANCIPATION IN THE CIVIL WAR ERA DEPICTED IN MOVIE LITTLE WOMEN - Ismi, Yulia Nurul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to find out the Emancipation of Women that occurred during the civil war era as depicted in the movie Little Women 2019. This study aims to find out the reasons behind the struggle for women's emancipation and the forms of struggle that were carried out to achieve the emancipation of women themselves. The 2019 Little Women movie is an adaptation of the novel of the same name by Louisa May Alcott which was first published in 1868, and the first movie adaptation was in 1933. The Little Women film was directed by Greta Gerwig. Even though the background is during the civil war, the values and messages regarding women's emancipation contained in this movie are still relevant to the present, so that this movie is still in great demand by many groups. From the results of this study, there are 25 research data found in the film Little Women 2019 by Greta Gerwig. Of these 25 data, 12 of them are used to explain the reasons behind women's struggle for emancipation. These 12 data are found in 3 out of 5 reasons behind women's struggle for emancipation in the civil war era depicted in the film Little Women 2019. Then, 13 other research data are used to explain the struggle for women's emancipation depicted in the movie Little Women 2019. Based on the reasons, found five reasons behind women's struggle for emancipation. Based on the form of the struggle, five forms of the struggle for women's emancipation were found. Based on this research, it can be concluded that the factors behind the occurrence of women's emancipation, as well as those that influenced the emancipation to occur, were very much influenced by the environment, both the family environment and the friendship environment.